REVIEW ON CURRENT TRENDS AND ADVANCEMENT IN DRUGS TRENDS AND DRUG TARGETS FOR TUBERCULOSIS THERAPY. - SUNNY JALHAN; ANIL JINDAL; AVNEET GUPTA; HEMRAJ (International Journal of Pharma and Bio Sciences, 2013)
Tuberculosis is today amongst the worldwide health threats. As resistant strains of Mycobacterium tuberculosis have slowly emerged, the failure of treatment is too often a fact, especially in countries lacking the necessary health care organization to provide the long and costly treatment have adapted by the patients. Because of lack of treatment or lack of adapted treatment, at least two million people are going to die this year. Due to this concern, this infectious disease was the focus of renewed scientiï¬c interest in the last decade. Regimens were optimized and much was learnt on the mechanisms of action of the antituberculosis drugs used. Despite advances in chemotherapy and the BCG (Bacillus Calmette–Guérin) vaccine, tuberculosis remains significant infectious disease. Although it can be cured the therapy takes at least 6–9 months and the laborious and lengthy treatment brings with it dangers of noncompliance, significant toxicity and drug resistance. The increasing emergence of drug resistance and the problem of mycobacterium persistence highlight the need to develop novel TB drugs that are active against drug resistant bacteria but, more importantly, kill persistent bacteria and shorten the length of treatment. Recent new and exciting developments in tuberculosis drug discovery show good promise of a possible revolution in the chemotherapy of tuberculosis